May-Thurner syndrome and iliac arteriovenous fistula in an elderly woman - Huynh, Nancy (J Vasc Surg Cases Innov Tech, 2016)
May-Thurner syndrome most commonly involves compression of the left common iliac vein by the right common iliac artery and can result in leg pain and swelling as well as potentially precipitate deep venous thrombosis. These symptoms can be exacerbated by additional vascular abnormalities. This is a case report of a 91-year-old woman with intractable massive left lower extremity edema that interfered with walking. She was diagnosed with concurrent May-Thurner syndrome and pelvic arteriovenous fistula. Treatment with embolization of the fistula and stenting of the left common iliac vein relieved her symptoms and allowed her to walk again.